PERAN MODAL SOSIAL DALAM PENGEMBANGAN PARIWISATA BERKELANJUTAN DI PANTAI ZAKAT KOTA BENGKULU - Putri Gunawan, Adelia Alfina; Heriyanti, Lesti; Wijayanti, Ayu (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2024)
Along with the times, the tourism sector is one of the factors that should be taken into account, because it is a strategic asset to encourage the development of areas that have natural potential or tourist attractions. Bengkulu City has a lot of natural tourism potential which, if managed properly, can improve the regional economy. One of them is Jakat beach tourism which has been around for a long time, managed by a tourism awareness group (Pokdarwis). Pokdarwis utilizes social capital as a strategy to manage the tourist destination